The Intra System Shift And Level Shift in English- Indonesian Subtitle Of Harry Potter and Sorcerer’s Stone Film by Chris Columbus - Santri, Merli; Azlan, Ulfatmi (English Language, Linguistics, Literature, And Education Journal, 2021)
The aim of this research is to describe what are the intra system shift and level shift in subtitle of Harry Potter and Sorcerer’s Stone Film by Chris Columbus, the causal of intra system shift and level shift in subtitle of Harry Potter and Sorcerer’s Stone Film by Chris Columbus, and which one is that more dominant between intra and level shift in subtitle of Harry Potter and Sorcerer’s Stone Film by Chris Columbus. Object in this research is Harry Potter and Sorcerer’s Stone Film by Chris Columbus. This research employs qualitative research with descriptive method. The object of this research is Harry Potter and Sorcerer’s Stone Film by Chris Columbus. The data used is subtitle in Harry Potter and Sorcerer’s Stone that contains intra system and level shift. The data is classified based on J.C. Catford theory about translation shift. They contain intra system shift, level shift, and the causal of intra system shift and level shift. The findings of research show about intra system shift. The researcher found all sentence that contained intra system shift, level shift, and causal of intra system shift and level shift that used by characters in Harry Potter and Sorcerer’s Stone, the intra system that was found in subtitle were 12 data, level shift that was found in subtitle were 10 data, and the causal of intra system shift and level shift that was found in subtitle were 7 data. In conclusion, intra system shift was mostly dominant used in sentence by characters in Harry Potter and Sorcerer’s Stone Film.